Ototopical gentamycin effects on rabbit middle ear and tympanic membrane - Koyuncu, M.; Celik, O.; Karadas, E.; Metin, N.; Yildirim, M.A. (My University, 1995)
The effects of ototopical antibiotic preparations on the middle ear (ME) and tympanic membrane (TM) have not been well recognized. In the present study, the effects of gentamycin (gentamycin sulphate 25 mg, benzalkonium chloride 0,5 mg) on the ME and TM of the rabbit were assessed microscopically after a single application of the solution to the ME through the transbulbar approach. Six controls, 15 experimental, making a total of 21 rabbits were studied. Animals were divided into 3 groups and were sacrificed at the 48th hour, 10th and 20th days. The specimens taken at 48th hour showed a mild epithelial hyperplasia, subepithelial oedema and hemorrhage in the ME. There were no significant pathological changes in the TM. In the specimens taken at the 10th day, mononuclear cell infiltration was observed in the subepithelial layer. The epidermal layer of the TM showed thickening, oedema and intraepithelial mononuclear cell infiltration. The fibrous layer of the TM was also thickened. At the 20th day, the mucosa of the ME was hemorrhagic, and mononuclear cell infiltration persisted in the subepithelial layer. Hyperplasia and fibrosis were moderate to severe in the mucosa of the ME. The findings indicated that gentamycin otic preparation might contribute to ME, TM complications when introduced into the ME cavity.
Keywords: gentamycin; middle ear; rabbits; tympanic membrane